Optimizing year-round fodder production for sustainable goat based integrated farming systems in the Yamuna ravines of Uttar Pradesh - ARIF, MOHD; POUROUCHOTTAMANE, R; KUMAR, ARVIND; KUMAR, RAVINDRA; RAI, B; GANGWAR, CHETNA; KUMAR, RAKESH; SINGH, M K; DIXIT, A K; GURURAJ, K (The Indian Journal of Agricultural Sciences, 2025)
The field experiment was conducted during the kharif and rabi seasons of 2020 and 2021 at ICAR-Central Institute for Research on Goats, Makhdoom, Mathura, Uttar Pradesh to optimize year-round fodder production for 20 goats and their 30 followers using one acre of land through the development of intercropping concept with different cereals and leguminous fodder crops; along with the implementation of good agricultural practices (GAP) during rainy (kharif) and winter (rabi) seasons. The technique demonstrated the potential to yield 7,600 kg of green fodder and 760 kg of maize grain from approximately one acre area during the kharif season. This output was sufficient to meet the green fodder requirements of the herd for six months. Similarly, during the rabi season, the technique produced 19,545 kg of green fodder and 652 kg of barley grain from one acre area, providing a surplus of green fodder and replacing over 85% of the barley requirement in concentrate feed for the herd over six months. The study highlights that by integrating intercropping strategies and GAP, goat farmers can sustainably produce the required green fodder and concentrate grain for a herd of 20 goats and 30 followers for a full year on just one acre of land.